Estimation of Distribution Function Parameters for Cases of Risk of Mortality Rate due to Malnutrition and Unhealthy Sanitation in Indonesia - Saputra, Moch Panji Agung; Megantara, Tubagus Robbi; Fitri, Sulidar (iora, 2022)
Child undernutrition is a significant problem in Indonesia; persistently high rates of stunting, underweight and wasting. Data about malnutrition and sanitation that taken for this research is data of age-standardized death rate, measured per 100,000 individuals from unsafe sanitation and malnutrition in Indonesia. The purpose of this research is to determine the distribution function and estimate the parameter distribution, so the values can provide identification of risk events. The method used for this research is Maximum Likelihood Estimation (MLE) and Newton Raphson iterations. The distribution function formed is gamma and Generalized Pareto Distribution (GPD), respectively for sanitation and malnutrition problems in Indonesia. The projected probability of occurrence of the risk of death due to malnutrition tends to be low in the future. So that the risk classification of the mortality rate due to malnutrition is considered low based on the results of the probability distribution approach on the GPD function. While, the projected probability of occurrence of the risk of death due to sanitation tends to decrease in the future. Based on the graph, the risk value with a high probability is around 20. So, the risk classification of the mortality rate due to malnutrition is considered moderate based on the results of the probability distribution approach on this gamma function.